Diet, risk of obesity and socioeconomic circumstances of individuals in the UK: A seemingly unrelated approach - Damilola Olajide; Anne Ludbrook (University of Oslo, 2012)
Understanding the link between diet, risk of obesity and the underlying socioeconomic circumstances of the individual is useful for health promotion and improvement interventions. In this study, we examined the socioeconomic factors that jointly affect food consumption choices and risk of obesity. We analyse the National Dietary and Nutrition Survey (2000/01) of adults aged 19-64 years living in private households in the UK, using a health production framework. We used information on the complete food history on individuals in the previous week to create eight common food groups. We estimated a system of linear risk of obesity (as measured by Body Mass Index) and eight diet equations with error terms that are correlated across equations for a given individual, but are uncorrelated across individuals, using the seemingly unrelated regression method. Our findings indicate that the socioeconomic factors (e.g. income and education) associated with sources of healthy eating differ. While increasing household purchasing power may be more effective for increasing consumption of healthier foods such as fruit and vegetables, more knowledge and information about healthy eating may be more effective for cutting down on consumption of less healthy foods (e.g. preserves and savoury foods). An understanding of these different healthy eating contexts is essential for the development of effective targeted food based policies aimed at reducing the risk of obesity. Link to Appendix